Five Cs as reflective learning attitude among Philippines nursing students - Acob, Joel Rey Ugsang; Setiya Dewi, Yulis; Arifin, Hidayat (Universitas Airlangga, 2022)
Introduction: Philosophical viewpoints from the first-hand source regarded as the best inception of COVID-19 knowledge are not widely explored. Humanity's understanding grounded on experiences becomes substantial only when stringent documentation of any events is performed carefully. COVID-19 as a phenomenon and as an ongoing struggle has myriad global impacts; hence the study aims to explore the understanding of nursing students' stances regarding the COVID-19 pandemic in their daily life. Methods: The study used a qualitative study design with online survey. A total of 41 nursing students were recruited through total sampling technique. The study was conducted to students in a university in the Philippines. Interview guidelines used open questions and were spread online. The data were subjected to thematic analysis. Results: The thematic analysis revealed five organizing themes, such as communication, commitment, care, collaboration, and change. Those themes were found among nursing students' stance regarding the COVID-19 phenomenon. Conclusions: The communication, commitment, care, collaboration, and change as development of a crisis-induced framework from study findings satisfies the essential finding that the pandemic is likewise giving rise to a new normal. Moreover, the results assist nursing students and other health-inspired domains to effectively maintain positivity amidst catastrophic climates.